Fisheries Cooperationin Tambov Province during 1920s - G. S. Makhrachev (Научный диалог)
This article examines the experience of regional cooperative development during the New Economic Policy (NEP) years. It focuses on the specifics of the unification of primary fisheries cooperatives into district and provincial unions. The author identifies two stages in this process: 1) from 1921 to 1924, when fisheries cooperatives had their own specialized unions; 2) from 1924 to 1928, when fisheries cooperation became part of mixed unions. The article presents data on the composition and number of cooperatives involved in the activities of these unions. It analyzes the functioning of the unions against the backdrop of changing realities, including the transition from War Communism to NEP, reduction of the province’s territory, the resolutions of the XIV All-Union Conference of the AllUnion Communist Party (Bolsheviks), and the III All-Union Congress of Soviets, as well as the adoption of a course towards industrialization. In conclusion, it is asserted that the gradual disappearance of specialized unions had a detrimental effect on cooperative development in the province. Most projects and initiatives developed and organized by the leadership of specialized unions were not fully realized. In mixed unions, attention to fisheries cooperation was given only as an afterthought.